E-Banking Payment Instruments and Deposit Money Banks’ Performance in Nigeria: An Empirical Investigation - Ughulu, Stephen E.; Agbonkhese, Abraham O. (Journal of Accounting, Business and Finance Research, 2020)
This paper carried out an empirical investigation of the impact of e-banking payment instruments on the performance of Deposit Money Banks (DMBs) in Nigeria for the period 2009 to 2017. The major findings of the paper showed that ATM exerted a negative effect on ROA but was significant at the 5% level; exerted a positive effect on ROE at the 5% level, and negative effect on NPM at the 5% level. POS exerted a negative effect on ROE but was significant at the 5% level; it exerted positive and significant impact on NPM; WB exerted positive and significant effect on ROA and NPM at the 5% level. These findings were robust and impressive as the value of the ECM(-1), -0.3988, -0.4857, -0.5863 and -22682 appeared with the right signs. The coefficients of determination, R2, in the three columns showed that all the independent variables accounted for over 50% fluctuations in the dependent variables. The paper concluded that e-banking payment instruments have great potentials in enhancing the performance of the DMBs. It was therefore recommended that the DMBs make it a matter of policy to continually upgrade the efficiency of these all-important instruments to meet the expectations and satisfaction of their clients and hence shareholders’ wealth.